Does Aid Matter? Measuring the Effect of Student Aid on College Attendance and Completion - Dynarski, Susan M (American Economic Review, 2003)
Does Aid Matter? Measuring the Effect of Student Aid on College Attendance and Completion by Susan M. Dynarski. Published in volume 93, issue 1, pages 279-288 of American Economic Review, March 2003